The Differences in Employees' Green Behavior Between Gender at PT Dewa Patria - Jenny, Ardhillah; Mellita, Dina; Fitriasuri; Elpanso, Efan (Journal Of Management Analytical and Solution (JoMAS), 2025)
This research aims to determine the effect of environmentally friendly recruitment selection, environmentally friendly training, environmentally friendly performance management, environmentally friendly payments & rewards, and environmentally friendly involvement on employee green behavior. The method used is quantitative. The purpose of this study is to examine the impact of gender differences on employees' green behavior at PT Dewa Patria. This research employs a quantitative method with descriptive analysis techniques. The sample consists of 88 employees from PT Dewa Patria. Data collection was conducted by distributing questionnaires to the employees. Data analysis involved normality tests and difference tests. The results indicate a significant statistical difference in green behavior among employees based on gender. In other words, gender has a significant impact on employees' green behavior.